Echocardiographic Global Longitudinal Strain Is Associated With Myocardial Fibrosis and Predicts Outcomes in Aortic Stenosis - Le, Thu-Thao; Huang, Weiting; Singh, Gurpreet K.; Toh, Desiree-Faye; Ewe, See Hooi; Tang, Hak Chaw; Loo, Germaine; Bryant, Jennifer A.; Ang, Briana; Tay, Edgar Lik-Wui; Soo, Wern Miin; Yip, James Wei-Luen; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims Left ventricular ejection fraction is the conventional measure used to guide heart failure management, regardless of underlying etiologies. Left ventricular global longitudinal strain (LV-GLS) by speckle tracking echocardiography (STE) is a more sensitive measure of intrinsic myocardial function. We aim to establish LV-GLS as a marker of replacement myocardial fibrosis on cardiovascular magnetic resonance (CMR) and validate the prognostic value of LV-GLS thresholds associated with fibrosis. Methods and results LV-GLS thresholds of replacement fibrosis were established in the derivation cohort: 151 patients (57±10 years; 58% males) with hypertension who underwent STE to measure LV-GLS and CMR. Prognostic value of the thresholds was validated in a separate outcome cohort: 261 patients with moderate-severe aortic stenosis (AS; 71±12 years; 58% males; NYHA functional class I-II) and preserved LVEF 50%. Primary outcome was a composite of cardiovascular mortality, heart failure hospitalization, and myocardial infarction. In the derivation cohort, LV-GLS demonstrated good discrimination (c-statistics 0.74 [0.66-0.83]; P<0.001) and calibration (Hosmer-Lemeshow 2= 6.37; P=0.605) for replacement fibrosis. In the outcome cohort, 47 events occurred over 16 [3.3, 42.2] months. Patients with LV-GLS >-15.0% (corresponding to 95% specificity to rule-in myocardial fibrosis) had the worst outcomes compared to patients with LV-GLS <-21.0% (corresponding to 95% sensitivity to rule-out myocardial fibrosis) and those between -21.0 and -15.0% (log-rank P<0.001). LV-GLS offered independent prognostic value over clinical variables, AS severity and echocardiographic LV mass and E/e’. Conclusion LV-GLS thresholds associated with replacement myocardial fibrosis is a novel approach to risk-stratify patients with AS and preserved LVEF.